LINGUOCULTURAL AND METHODICAL FOUNDATIONS OF TEACHING AXIOLOGICAL UNITS IN ENGLISH AND UZBEK LANGUAGES ("Conference on Universal Science Research 2023", 2026)
This article examines the linguocultural and methodical foundations of teaching axiological units — value-laden words, phrases, and expressions — in English and Uzbek. Axiological units reflect the moral, ethical, and emotional values embedded in a language community’s worldview. The study identifies key differences and similarities in how values are linguistically encoded in both languages.